Acute effects of small changes in crank length on gross efficiency and pedalling technique during submaximal cycling - Ferrer-Roca, V.; Rivero-Palomo, V.; Ogueta-Alday, A.; Rodriguez-Marroyo, J. A.; Garcia-Lopez, J. (Journal of Sports Sciences, 2017)
The main purpose of this study was to assess the acute effects of small changes in crank length (assumable by competitive cyclists) on metabolic cost and pedalling technique during submaximal cycling. Twelve amateur road cyclists performed three sets of submaximal pedalling (150, 200 and 250 W) at a constant cadence (91.3 ± 0.8 rpm) in a randomised order with three commonly used crank lengths, preferred (172.5-175 mm), +5 mm and -5 mm. Energy cost of pedalling, kinetic and kinematic variables were simultaneously registered. Changes in crank length had no significant effect on heart rate (144 ± 13, 145 ± 12 and 145 ± 13 bpm, respectively) and gross efficiency (GE) (20.4 ± 2.1, 20.1 ± 2.2 and 20.3 ± 2.4%, respectively). A longer crank induced a significant (P < 0.05) reduction of positive impulse proportion (PIP) (0.9-1.9%) due to a greater maximum (1.0-2.3 N · m) and minimum torque (1.0-2.2 N · m). At the same time, the maximum flexion and range of motion of the hip and knee joints were significantly increased (1.8-3.4° and P < 0.05), whereas the ankle joint was not affected. In conclusion, the biomechanical changes due to a longer crank did not alter the metabolic cost of pedalling, although they could have long-term adverse effects. Therefore, in case of doubt between two lengths, the shorter one might be recommended